Effects of Shenmai injection on the values of CO, SV, and EF in patients undergoing off-pump coronary artery bypass graft: A randomized, clinical trial. Issue 10 (March 2018) - Liu, Qingxue; Wu, Haiyan; Wang, Jianjuan; Li, Xi-ming
Abstract: Background: To explore the effects of Shenmai (SM) injection on the values of cardiac output (CO), stroke volume (SV), and the ejection fraction (EF) in patients treated with off-pump coronary artery bypass graft (OPCABG). Methods: Forty patients undergoing OPCABG were randomly divided into SM group (n = 20) and the 5% glucose (G) group (n = 20). The control liquids were injected from the beginning of the operation to the start of coronary artery bypass graft (CABG). The values of CO, SV, and EF before induction (t1 ), at the beginning of operation (t2 ), 30 minutes after the start of operation (t3 ), at the beginning of coronary artery bypass graft (t4 ), at the end of coronary artery bypass graft (CABG) (t5 ), and at the end of operation (t6 ) were recorded. Results: The values of CO, SV, and EF in the patients of SM group at t3 to t6 were found to be significantly higher than those at t1 ( P < .05). The values of CO, SV, and EF in the patients of G group were found to be increased at t5 and t6 ( P < .05). At t3 and t4, the values of CO, SV, and EF in SM group were significantly higher than those in the G group ( P < .05). Conclusion: In patients with OPCABG, the infusion of SM injection can effectively increase the values of CO, SV, and EF and increase the safety of anesthesia management.